Effects of Task Complexity on L2 Writing Behaviors and Linguistic Complexity. Issue 1 (28th August 2016) - Révész, Andrea; Kourtali, Nektaria‐Efstathia; Mazgutova, Diana
Abstract: This study investigated whether task complexity influences second language (L2) writers' fluency, pausing, and revision behaviors and the cognitive processes underlying these behaviors; whether task complexity affects linguistic complexity of written output; and whether relationships between writing behaviors and linguistic complexity are moderated by task complexity. Participants were 73 advanced L2 writers, who completed simple or complex essay tasks. Task complexity was operationalized as the absence versus presence of content support. Participants' writing behaviors were recorded via keystroke logging software. Four writers, drawn from groups performing simple and complex tasks, additionally engaged in stimulated recall. Content support was found to lead to less pausing, more revision, and increased linguistic complexity. When content support was absent, more frequent pauses and revisions were associated with less sophisticated lexis. These results, combined with stimulated recall comments, suggest that content support likely reduced processing burden on planning processes, facilitating attention to linguistic encoding. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .